PENGARUH DEWAN KOMISARIS, DEWAN DIREKSI, DAN DEWAN PENGAWAS SYARIAH TERHADAP PENGHINDARAN PAJAK PADA PERBANKAN SYARIAH DI INDONESIA PERIODE 2020–2024 - Karnila Putri; Usdeldi Usdeldi; Atar Satria Fikri (Nusantara Hasana Journal, 2026)
This study aims to analyze the effect of the Board of Commissioners, Board of Directors, and Sharia Supervisory Board on tax avoidance in Islamic banking in Indonesia during the 2020–2024 period. The study is motivated by the low Effective Tax Rate (ETR), which indicates tax avoidance practices, and the suboptimal implementation of corporate governance in Islamic banking. This research employs a quantitative approach with a causal associative design. The data used are secondary data derived from financial statements of 10 Islamic commercial banks registered with the Financial Services Authority (OJK). The analysis method used is panel data regression. The results show that the Board of Commissioners and Board of Directors have a positive effect on tax avoidance, while the Sharia Supervisory Board has a negative effect. Simultaneously, all variables significantly influence tax avoidance. These findings indicate that corporate governance plays an important role in determining corporate tax policies.